Relationship between Knowledge Level and Anxiety Facing Childbirth in Primiparous Mothers at Panembahan Senopati Hospital Bantul - Maria Julieta Esperanca Naibili; Sri Sat Titi Hamranani; Melania Wahyuningsih (Journal of Nursing Science Update (JNSU), 2022)
The 7 “P” factors influencing the child-birth process are “Power”, ”Passage”, “Passenger”, “Psyche”, ”Pain”, “Patience”, and  “Position”. Psyche includes anxiety, which for laboring mothers creates tension, vasoconstriction in uterine blood vessels, pain, reduced uterine contraction, and delayed cervical opening so that childbirth takes longer. Long childbirth or partus can increase mothers' and babies' morbidity and mortality rates. This research aimed to identify the correlation between Knowledge Level and Anxiety Facing Childbirth in Primiparous Mothers at Panembahan Senopati Hospital Bantul. This study was quantitative research with a descriptive-analytic design using the cross-sectional approach. The population in this research consisted of 145 primipara mothers, with purposive sampling of 59 respondents. The data were collected with a questionnaire and analyzed with the Spearman Rank Correlation Test. The respondents’ knowledge level belonged to the ‘good’ category, 96.6%, while the anxiety level among the primipara mothers belonged to the ‘moderate’ category, 79.7%. The analysis of the correlation between the knowledge level and the anxiety level among Primipara mothers in Panembahan Senopati Hospital Bantul resulted in a p-value = 0.001 with a Rho-Spearman correlation value of -0,415. There was a moderate correlation between knowledge and anxiety levels among primipara mothers in Panembahan Senopati Hospital Bantul.  Healthcare providers can promote the seven essential power education models of childbirth ("Power," "Passage," "Passenger," "Psyche," "Position," "Pain," and "Patience") in maternity nursing practice so that nurses can pay attention to the complexities of care holistically for women who give birth